Modeling oxyanion adsorption on ferralic soil, part 1: Parameter validation with phosphate ion. (14th July 2014) - Pérez, Claudio; Antelo, Juan; Fiol, Sarah; Arce, Florencio
Abstract Surface complexation models have proved to be valuable tools for predicting processes that occur at the solid–solution interface. Use of such models has become more widespread and nowadays more complex systems are studied, in an attempt to explain processes such as the competition between different species for mineral surfaces and the effect of the presence of organic matter. The aim of the present study was to analyze the mobility of phosphate in ferralic soils. The charge distribution model parameters for phosphate–goethite adsorption were used to predict phosphate mobility on samples from 2 horizons of a ferralic soil containing large amounts of iron oxides. The soil reactivity was attributed to the iron oxides, and some specific parameters were determined by means of phosphate adsorption–desorption experiments and included in the model. Adsorption of phosphate in the upper horizon, which contained more organic carbon and phosphate than the deeper one, was modeled by using the information obtained for the soil and the charge distribution model parameters derived for phosphate–goethite interaction with no need of further optimization. In contrast, some extra fitting parameters were required to improve the modeling of the phosphate adsorption in the deeper horizon. Environ Toxicol Chem 2014;33:2208–2216. © 2014 SETAC